LOST IN TRANSLATION: THE VERBAL CHANGE FROM PERSONA TO PERSON - WU, Tzung-Mou (Comparative Legilinguistics, 2017)
This paper challenges the modern legal concept of “person” by analyzing the translation problems of some Roman law fragments. It shows why the Latin word “persona” cannot be the etymon of the vernacular “person,” and argues that the modern use of “person” stems from the nineteenth-century German juridical literature, especially that of F. C. von Savigny. This paper shows that “persona” forms a phrase with verbs like gerere, tenere and sustinere (bear, carry, hold, etc.) and has no meaning by itself. Such phrases require a noun complement in genitive form, as their synonym “represent,” which is transitive, needs a direct object. On the other hand, the modern literature attributes a sense to “person,” taking it as equivalent to “human individual” and using it word with the verb “be.” This use is a modern invention and cannot be re-translated into Latin without semantic confusion.